A redação do Enem 2017 : um olhar Bakhtiniano sobre o atendimento ao tema por alunos de uma escola pública de Cuiabá - Moraes, Suleima Cristina Leite de (2018)
This research proposes to discuss the insufficient results achieved by the Brazilian young people in the written exam of the National High School Examination (Enem) and to reflect on the possible causes for this inefficiency, especially those related to attending the proposed topic, one of the five competencies required in the Matrix in this test. From a reading in the indicators of the National Institute of Anísio Teixeira Research for the Exams carried out in the period from 2013 to 2015, it was observed that the grades attributed to the two lower levels of Competence 2, which evaluates the comprehension of the proposed theme in the limits of a dissertation-argumentative text, are very high. Considering that only an adequate understanding of the subject can guarantee the discursive domain of the candidate in the formulation of his discourse, he started with the following research questions: 1. What do the candidate students understand by "attending to the subject"? And: How is this understanding reflected in the text produced? 2. Why the thematic understanding presents high indices of low grades in the writing of the Enem? 3. What knowledge do students and teachers have of the criteria required by the Notice for the evaluation of Competence II? To answer these questions, we conducted a case study at the "Maria de Arruda Muller" Liceu Cuiabano State School, located in the central region of Cuiabá-MT, following three phases as methodological steps: in the first, two questionnaires were developed the generation of data: Questionnaire I, for the Director of the School Unit, and Questionnaire III, directed to the students enrolled in the 3rd year with questions related to the Writing Test of the Enem; in the second phase, after the second semester of the school year, Questionnaire II was applied, aimed at teachers who work with the third years with questions related to the Enem's requirements for writing, especially about their understanding of Competence 2. Finally, in the third stage, we seek to sensitize the students to contribute with the research with the availability of the texts that would develop in the test, which we take for analysis. Taking the reflections and debates proposed in the conceptions of interaction, dialogism and in the concept of active understanding of Bakhtin and his Circle, we used the essays produced in the 2017 Exam to try to find out how the theme was worked. It was observed, with the interpretation of the questionnaires and the analysis of the 12 essays collected, that the candidates actively dialogued with the proposed theme, expressing themselves critically about the problem raised and not only taking the theme as a topic or subject to be unreflectively repeated, which indicated that the low results in the essays are not related to the ignorance of what it is to attend to the subject or of the limited understanding that it is only the topic or subject that must be approached. The reflections and debates presented aim to contribute to the development of a writing practice in High School to be closer to the discursive reality of the students, as a way to make them more competent in the dialogical relationship with the world and certainly with the texts.